Angelman syndrome: clinical findings and follow-up data of 14 patients - Kara, Bülent; Karaman, Birsen; Ozmen, Meral; Rosti, Rasim Ozgür; Calişkan, Mine; Kayserili, Hülya; Başaran, Seher (The Turkish Journal of Pediatrics, 2008)
The diagnosis of Angelman syndrome (AS) is based on the clinical features, behavior, EEG findings, and genetic abnormalities. The physical, clinical and behavioral aspects appear to attributable to localized central nervous system (CNS) dysfunction of the ubiquitin ligase gene, UBE3A, located at 15q11.2. The features of AS frequently become apparent at 1-4 years of age, and the average age at diagnosis is 6 years. Angelman syndrome was considered in the differential diagnosis of 30 patients who were referred to the Medical Genetics Department of Istanbul Medical Faculty between 1995 and 2005. The diagnosis was confirmed in 14 patients (8 female, 6 male) by detecting the presence of deletion through the use of fluorescence in situ hybridization (FISH) technique in all, while high-resolution banding technique (HRBT) detected only seven of the deletions. The patients’ ages at the time of diagnosis ranged from 2 to 12 (mean 4.10+/-2.59) years. We report here on 14 patients with definite diagnosis of AS who displayed the characteristic clinical features of the syndrome and additional findings not previously reported, along with the follow-up data concerning neuromotor development and seizures.